Sensorless field oriented control of nonsinusoidal flux-distribution permanent magnet synchronous motor with a FEM based ANN observer - Oksuztepe, Eyyup; Omac, Zeki; Polat, Mehmet; Celik, Hakan; Selcuk, Ahmet Hakan; Kurum, Hasan (Tubitak Scientific & Technological Research Council Turkey, 2016)
The sensorless vector control of a nonsinusoidal flux -distribution permanent magnet synchronous motor (PMSM) has been performed by a trained artificial neural network (ANN) using flux data obtained from the finite element method (FEM). A more sensitive rotor position has been estimated by using the fluxes of each of the three phases of the PMSM. In the proposed approach, magnet flux of the nonsinusoidal PMSM has been calculated by FEM for every single degree. Rotor position and speed values have been estimated by training an ANN with this information. The experimental results obtained by DS1103 development kit have proved the validity of the proposed approach.
Keywords: PMSM; sensorless Control; DSP; AC drivers